Spinal Cord Injuries Secondary to Mountain Biking Accidents — A Cause for National Alarm - William Chu Kwan; Pedram Laghaei; Harsh Kahlon; Tamir Ailon; Raphaële Charest-Morin; Charlotte Dandurand; Scott Paquette; Nicolas Dea; John Street; Charles G. Fisher; Vanessa Noonan; Marcel F. Dvorak; et al. (Neurotrauma Reports)
While much attention in North America has been placed on hockey and other high impact sports as causes of spinal cord injury (SCI), over the past two decades, our Level 1 trauma center has experienced a much higher number of SCI from off-road mountain biking (MTB). Here, we aimed to characterize the epidemiology of SCI secondary to MTB, and we also sought to estimate the direct and other economic costs to assess their societal impact. A retrospective review was conducted of patients with SCI from MTB who were treated at our Level 1 trauma center between 2008 and 2022. Injury details were compiled, and we calculated the associated lifetime direct and other costs. Over the 14-year period, we identified 58 individuals (average age 35.5 years, 93% male) who suffered SCI while MTB. Twenty-seven suffered motor complete SCI (14 tetraplegia, 13 paraplegia) with estimated average lifetime costs in Canadian Dollars of $4.8 M and $4.5 M each, respectively. Thirty-one suffered motor incomplete SCI (26 tetraplegia, 5 paraplegia) with estimated average lifetime costs of $2.4 M and $1.6 M each, respectively. The total estimated lifetime costs for this group of SCI individuals were $195.4 M. From 2008 to 2022, we identified an SCI from MTB accidents at a rate of 4 patients per year. Our data underscores the urgent need for increased awareness and preventive measures to reduce the incidence of these devastating injuries, particularly in regions where MTB is prevalent.